Risk factors of pre-marital sexual activities among female adolescents in Kuala Lumpur, 1995 - Rusilawati Jaudin,; Khadijah Shamsudin, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Pre-marital sexual activities among adolescents in developing countries including Malaysia are becoming greater concerns. A case control study was conducted to assess the risk factors of pre-marital sexual activities among female adolescents aged 11-20 years in Kuala Lumpur. Fourty five female inmates from Kuala Lumpur who were placed at the Pusat Pemulihan Akhlak, Rembau, Negeri Sembilan were compared with 50 students from a school in Kuala Lumpur which was randomly selected for this study. Intoffi1ation were gathered via self-administered questionaire. The results show significant associations between premarital sexual activities and the respondents' level of education, age of puberty, household size, mother's working status, time spent with parents during school holidays, presence of special boy friend as well 30') reading and watching pornographic materials ( p values < 0.05 ). The odds ratio of involvement in premarital sex activities among cases compared to controls are 27.8 and 12.4 for exposure to pornographic books and movies respectively, 11.2 for lack of parental interactions, 4.6 for having special boyfriend and 3.6 if. their mothers are working. The odds ratio of exposure to pornographic reading materials after controlling other risk factors show a significant change. Mother who is not working and spending time together with children are among the factor which help in preventing sexual activities among unmarried adolescent girls, though they were exposed to pornographic materials.